ESOPE-Equivalent Pulsing Protocols for Calcium Electroporation: An In Vitro Optimization Study on 2 Cancer Cell Models. (18th July 2018) - Romeo, Stefania; Sannino, Anna; Scarfì, Maria Rosaria; Vernier, P. Thomas; Cadossi, Ruggero; Gehl, Julie; Zeni, Olga
Reversible electroporation is used to increase the uptake of chemotherapeutic drugs in local tumor treatment (electrochemotherapy) by applying the pulsing protocol (8 rectangular pulses, 1000 V/cm, 100 µs) standardized in the framework of the European Standard Operating Procedure on Electrochemotherapy multicenter trial. Currently, new electrochemotherapy strategies are under development to extend its applicability to tumors with different histology. Electrical parameters and drug type are critical factors. A possible approach is to test pulse parameters different from European Standard Operating Procedure on Electrochemotherapy but with comparable electroporation yield (European Standard Operating Procedure on Electrochemotherapy-equivalent protocols). Moreover, the use of non-toxic drugs combined with electroporation represents the new frontier for electrochemotherapy applications; calcium electroporation has been recently proposed as a simple tool for anticancer therapy. In vitro investigations facilitate the optimization of electrical parameters and drugs for in vivo and clinical testing. In this optimization study, new pulsing protocols have been tested by increasing the pulse number and reducing the electric field with respect to the standard. European Standard Operating Procedure on Electrochemotherapy-equivalent protocols have been identified in HL-60 and A431 cancer cell models, and a higher sensitivity in terms of electroporation yield has been recorded in HL-60 cells. Moreover, cell killing efficacy of European Standard Operating Procedure on Electrochemotherapy-equivalent protocols has been demonstrated in the presence of increasing calcium concentrations on both cell lines. Equivalent European Standard Operating Procedure on Electrochemotherapy protocols can be used to optimize the therapeutic effects in the clinic, where different regions of the same cancer tissue, with different electrical properties, might result in a differential electroporation yield of the standard protocol over the same tissue, or, eventually, in an override of the operational limits of the instrument. Moreover, using calcium can help overcome the drawbacks of standard drugs (side effects, high costs, difficult handling, preparation, and storage procedures). These results support the possibility of new treatment options in both standard electrochemotherapy and calcium electroporation, with clear advantages in the clinic.